2002
DOI: 10.1067/mva.2002.121571
|View full text |Cite
|
Sign up to set email alerts
|

Epidural cooling for the prevention of ischemic injury to the spinal cord during aortic occlusion in a rabbit model: Determination of the optimal temperature

Abstract: These study results suggest that in rabbits satisfactory spinal cord protection during aortic occlusion can be achieved at moderate regional hypothermia (24 degrees C). Large volume infusion for the achievement of profound hypothermia may cause deleterious effects of increased ICP and is not warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…12 The moderate levels of hypothermia (mean Ϸ26°C) achieved in the at-risk thoracolumbar cord with this method have repeatedly been demonstrated to be protective. 29,34 Similar to the results of others reporting longitudinal experience assessing the impact of adjuncts for cord protection, 8 we could demonstrate that EC had a significant impact on SCI when compared to institutional, historical controls. 35 An identical, statistically significant impact on SCI in patients treated for types I-III TAA was noted in the present study.…”
Section: Discussionsupporting
confidence: 78%
“…12 The moderate levels of hypothermia (mean Ϸ26°C) achieved in the at-risk thoracolumbar cord with this method have repeatedly been demonstrated to be protective. 29,34 Similar to the results of others reporting longitudinal experience assessing the impact of adjuncts for cord protection, 8 we could demonstrate that EC had a significant impact on SCI when compared to institutional, historical controls. 35 An identical, statistically significant impact on SCI in patients treated for types I-III TAA was noted in the present study.…”
Section: Discussionsupporting
confidence: 78%
“…The examination included a count of the viable neurons per section in the ventral gray matter and a graded histological damage scoring (Table I). 13 Slides were examined by a pathologist blinded to the experimental protocol. Readings from 3 sections were taken and values were averaged at 24, 72, and 120 hours after reperfusion.…”
Section: Methodsmentioning
confidence: 99%
“…Several experiments have demonstrated that regional cooling by infusing cold saline into the intrathecal or epidural space protects against ischemic spinal cord insult. [43][44][45] Cambria et al 46 and Tabayashi et al 47 described favorable clinical results of this procedure. However, it might cause a detrimental increase in CSF pressure.…”
Section: Mild Hypothermiamentioning
confidence: 88%